Penyelesaian Sengketa Harta Bersama Secara Mediasi - Setyaranti Utami, Tiara; Suhermi, Suhermi; Sasmiar, Sasmiar (Universitas Jambi, Fakultas Hukum, 2023)
The purpose of this study was to find out and analyze the implementation of joint property dispute resolution through mediation and its constraints at the Muara Bungo Religious Court. The problem is how to implement the settlement of joint property disputes and the obstacles in solving them at the Muara Bungo Religious Court. This research is an empirical juridical research using primary data and secondary data. The results of the study showed that there were 17 cases of settlement of joint property disputes through mediation at the Muara Bungo Religious Court for the 2019-2022 period, 8 successful mediations and 9 unsuccessful ones. Overall the mediation process at the Muara Bungo Religious Court was carried out as stipulated in PERMA No. 1 of 2016. The results of this mediation were 2 (two), namely successful mediation and unsuccessful mediation. The obstacles that arise in the unsuccessful implementation of joint property dispute resolution at the Muara Bungo Religious Court are the lack of good faith such as the absence of the parties at mediation and it is difficult to reconcile because they do not reach an agreement between the two parties, then from the institution the lack of certified mediators, and there are still people who do not know the purpose or benefits of mediation. Abstrak Tujuan penelitian ini untuk mengetahui dan menganalisis pelaksanaan penyelesaian sengketa harta bersama melalui mediasi dan kendalanya di Pengadilan Agama Muara Bungo. Permasalahannya bagaimana pelaksanaan penyelesaian sengketa harta bersama dan kendala dalam penyelesaiannya di pengadilan Agama Muara Bungo. Penelitian ini merupakan penelitian yuridis empiris dengan menggunakan data primer dan data sekunder. Hasil penelitian bahwa penyelesaian sengketa harta bersama melalui mediasi di Pengadilan Agama Muara Bungo periode tahun 2019-2022 sebanyak 17 kasus, mediasi yang berhasil sebanyak 8 dan yang tidak berhasil sebanyak 9, secara keseluruhan proses mediasi di Pengadilan Agama Muara Bungo dilaksanakan sebagaimana yang diatur dalam PERMA No. 1 Tahun 2016. Hasil dari mediasi ini ada 2 (dua), yaitu mediasi yang berhasil dan mediasi yang tidak berhasil. Adapun kendala yang timbul dalam ketidakberhasilan pelaksanaan penyelesaian sengketa harta bersama di Pengadilan Agama Muara Bungo yakni tidak adanya itikad baik seperti ketidakhadiran para pihak pada saat mediasi dan sulit untuk didamaikan karena tidak mencapai kata sepakat antara kedua belah pihak, kemudian dari pihak lembaga kurangnya mediator bersertifikat, serta masih adanya masyarakat yang belum mengetahui tujuan maupun manfaat dilakukannya mediasi.